1984
DOI: 10.2527/jas1984.5951256x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a β-Adrenergic Agonist to Alter Muscle and Fat Deposition in Lambs1

Abstract: The present invention relates to therapeutic uses of clen buterol in humans and animals. The uses include retarding or reversing muscular atrophy of denervated muscle, alleviat ing or reversing loss of function arising from surgical or accidental muscular trauma, and alleviating or reversing the loss of muscle function arising from a humorally mediated catabolic state or from temporary disuse of the muscle. Clenbuterol can be mixed with a beta-adrenergic antagonist to obviate or mitigate unwanted side effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(60 citation statements)
references
References 11 publications
7
50
0
1
Order By: Relevance
“…These effects were subsequently confirmed in swine (Ricks et al 1984a), steers (Ricks et al 1984b) and lambs (Baker et al 1984) and have since undergone intense scrutiny and experimental testing by the swine industry (Anderson et al 1987; Bergen et al Hancock et al 1987; Merkel et al 1987; Veenhuizen et al 1987; Watkins et al 1989).…”
Section: T6mentioning
confidence: 91%
“…These effects were subsequently confirmed in swine (Ricks et al 1984a), steers (Ricks et al 1984b) and lambs (Baker et al 1984) and have since undergone intense scrutiny and experimental testing by the swine industry (Anderson et al 1987; Bergen et al Hancock et al 1987; Merkel et al 1987; Veenhuizen et al 1987; Watkins et al 1989).…”
Section: T6mentioning
confidence: 91%
“…Leurs effets «répartiteurs» provoquent une modification de la composition des carcasses qui correspond à une diminution des dépôts adipeux, associée à un accroissement de la masse protéique (Lafontan ef al, 1988). Ces résultats ont été observés chez plusieurs espèces animales : ovins (Baker et al, 1984); porcins (Moser et al, 1986), et bovins (Miller et al, 1988).…”
Section: Introductionunclassified
“…Some studies indicated that the activity of calpastatin, the endogenous inhibitor of μ-and m-calpain, increases substantially during supplementation with type 2 β-agonists (25), whereas others have suggested that improvements in protein accretion are due to an increase in protein. Like the present study, Baker et al (26) reported an increase in protein and moisture content with a reduction in fat content in the hindquarter muscle of lambs fed clenbuterol (a β-agonist type 2). Byrem et al (27) evaluated the direct action of a type 2 β-agonist on muscle protein accretion in vivo by closed arterial infusion of cimaterol into a single hindlimb for 21 days in growing steers.…”
Section: Lm Chemical and Qualitative Characteristicsmentioning
confidence: 58%
“…Supplementation with a type 2 β-agonist caused a decrease in visceral organ mass (gastrointestinal tract and/or liver) in rats (30). Similarly, a reduction in kidney (7.5%) and heart (15.4%) mass was previously reported in lambs fed with type 2 β-agonist cimaterol (26). ZH supplementation decreased liver weight by 9.5% in lambs (12).…”
Section: Visceral Organs Massmentioning
confidence: 74%
See 1 more Smart Citation